The Modification and Validation of the Medication Compliance Questionnaire (MCQ) for the Assessment of Adherence to Antiretroviral Therapy (ART) - Mustafa, Suzana; Azmi, Nazmi Liana; Hassan, Norul Badriah; Wan Yusuf, Wan Nazirah (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Anti-retroviral therapy (ART) significantly improves the prognosis of human immunodeficiency virus (HIV) infection. Yet long-term and complex regimens often lead to non-adherence. Maintaining at least 95% adherence is crucial for effective ART and thus preventing drug resistance. The Medication Compliance Questionnaire (MCQ) has been used for adherence assessment in antihypertensive treatment, with an 80% cut-off level. This study aimed to modify and validate the MCQ for assessing adherence to ART. MATERIALS AND METHODS: The MCQ underwent modification with the incorporation of a new rating scale and scoring method. A pilot study was conducted at the Infectious Disease Clinic, Hospital Raja Perempuan Zainab II, Kelantan. Inclusion criteria were adults living with HIV (PLHIV), on ART for at least two months and who can communicate in Malay. Fisher’s Exact test was used to determine validity, sensitivity, and specificity. Cronbach’s alpha and intra-class correlation coefficients were used to evaluate reliability, with significance set at p <0.05. RESULTS: A total of 60 PLHIV adults participated in this pilot study. Viral load served as the validity criterion for the modified MCQ, showing a significant association with adherence (p=0.018). Sensitivity and specificity values were 100.0% and 79.5%, respectively. Cronbach’s alpha coefficients for drug-taking and drug-stopping behaviour domains were 0.65 and 0.90, respectively. CONCLUSION: The modified MCQ is a valid and reliable tool for assessing adherence to ART, demonstrating high sensitivity and adequate specificity. It is suitable for use in clinical practice to improve medication therapy management for PLHIV